Preoperative Anxiolysis and Treatment Expectation (PATE Trial): open-label placebo treatment to reduce preoperative anxiety in female patients undergoing gynecological laparoscopic surgery – study protocol for a bicentric, prospective, randomized-controlled trial - Wessels, Johannes; Klinger, Regine; Benson, Sven; Brenner, Thorsten; Elsenbruch, Sigrid; Aulenkamp, Jana L. (Frontiers in Psychiatry, 2024)
One of the most common concerns of patients undergoing surgery is preoperative anxiety, with a prevalence of up to 48%. The effects of preoperative anxiety continue beyond the preoperative period and are associated with more severe postoperative pain and poorer treatment outcomes. Treatment options for preoperative anxiety are often limited as sedatives cause side effects and their efficacy remains controversial. Placebo research has shown that optimization of positive treatment expectations, as can be achieved through placebo administration and education, has clinically relevant effects on preoperative anxiety, pain and treatment outcomes. As the administration of masked placebos raises ethical questions, clinical studies have increasingly focused on the use of open, non-deceptive placebo administration (open-label placebo, OLP). The use of OLPs to reduce preoperative anxiety and modify clinically relevant postoperative outcomes has not yet been investigated. This bicentric, prospective, randomized-controlled clinical trial (PATE Trial; German Registry for Clinical Studies DRKS00033221), an associated project of the Collaborative Research Center (CRC) 289 “Treatment Expectation”, aims to alleviate preoperative anxiety by optimizing positive treatment expectations facilitated by OLP. Furthermore, this study examines a potential enhancement of these effects through aspects of observational learning, operationalized by a positive expectation-enhancing video. In addition, patient’s perspective on the self-efficacy and appropriateness of OLPs prior to surgery will be assessed. To achieve these objectives, female patients will be randomized into three groups before undergoing gynecological laparoscopic surgery. One group receives the OLP with a positive rationale conveyed by a study physician. A second group receives the same intervention, OLP administration and rationale provided by a physician, and additionally watches a video on OLP presenting a satisfied patient. A third group receives standard treatment as usual (TAU). Outcome measures will be effects on preoperative anxiety and postoperative experience, particularly visceral and somatic postoperative pain. As the non-deceptive administration of placebos; when indicated; may yield positive outcomes without side effects, and as current treatment of preoperative anxiety is limited, evidence from clinical placebo research has the potential to improve outcomes and patient experience in the surgical setting.